Estimating liquefaction potential of sands using the piezovane - Scott, Clinton E., author; Charlie, Wayne A., advisor; Doehring, D. O., committee member; Siller, T. J., committee member (Colorado State University. Libraries, 1989)
Laboratory test results are presented indicating feasibility of estimating liquefaction potential of saturated cohesionless soil using the piezovane, a shear vane incorporating pore pressure measurement. Utilizing a calibration chamber, piezovane shear tests are conducted on medium-fine subrounded quartz sand. Partially drained tests show small negative pore pressure peaks in dense samples and small positive peaks in relatively loose samples, indicating a reasonable trend of volumetric strain tendencies during shear. The piezovane induces positive pore pressure at denser initial states than steady states (zero contraction) determined by CU triaxial tests, but peak shear strength trends and direct shear test results indicate that observed pore pressure response adequately reflects actual contractive and dilative tendencies during piezovane shear.
Covers not scanned.
Keywords: Soil liquefaction; Soil mechanics; Sand